2003
DOI: 10.1038/sj.ejcn.1601503
|View full text |Cite
|
Sign up to set email alerts
|

Socio-economic status, dietary intake and 10 y trends: the Dutch National Food Consumption Survey

Abstract: Objective: To study differences in dietary intake between adults with different socioeconomic status (SES) and trends over time. Design: Cross-sectional study based on data of three Dutch National Food Consumption Surveys (DNFCS-1 1987=88; DNFCS-2 1992; DNFCS-3 1997=98), obtained from a panel by a stratified probability sample of the non-institutionalized Dutch population. Subjects: A total of 6008 men and 6957 women aged 19 y and over. Methods: Dietary intake was assessed with a 2 day dietary record. Backgrou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

25
283
12
16

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 364 publications
(336 citation statements)
references
References 25 publications
25
283
12
16
Order By: Relevance
“…First, it extends findings from previous reports that showed a positive relationship between income, education and diet quality (Groth et al, 2001;Bodnar and Siega-Riz, 2002;Friel et al, 2003;Hulshof et al, 2003). Second, we used a large nationally representative dataset with a wealth of social, demographic, psychosocial and nutritional information.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…First, it extends findings from previous reports that showed a positive relationship between income, education and diet quality (Groth et al, 2001;Bodnar and Siega-Riz, 2002;Friel et al, 2003;Hulshof et al, 2003). Second, we used a large nationally representative dataset with a wealth of social, demographic, psychosocial and nutritional information.…”
Section: Discussionmentioning
confidence: 72%
“…Moreover, previous studies have shown that socio-economic status (SES) was positively related to indicators and indices of diet quality (Groth et al, 2001;Bodnar and Siega-Riz, 2002;Friel et al, 2003;Hulshof et al, 2003;Giskes et al, 2004). In our present study, we hypothesized that this positive relationship varies across ethnic and gender groups in the United States.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…Most previous studies have examined differences in food habits focusing only on one or few indicators of socio-economic position, typically educational level, occupational class or income. According to these studies, those in higher socio-economic positions are more likely to follow healthier food habits (Hulshof et al, 1991;IralaEstévez et al, 2000;Groth et al, 2001;Hulshof et al, 2003;Martikainen et al, 2003;Shahar et al, 2005). However, evidence on the interrelationships and pathways between socio-economic circumstances as determinants of food habits is scarce.…”
Section: Introductionmentioning
confidence: 99%
“…This is true especially for people with lower socio-economic status (SES) (1)(2)(3) . Much research has focused on this topic and revealed several determinants that may explain this phenomenon.…”
mentioning
confidence: 99%